2015
DOI: 10.1007/s11356-015-5623-z
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic speciation in rice and risk assessment of inorganic arsenic in Taiwan population

Abstract: This study assessed the total arsenic content and arsenic speciation in rice to determine the health risks associated with rice consumption in various age-gender subgroups in Taiwan. The average total arsenic levels in white rice and brown rice were 116.6 ± 39.2 and 215.5 ± 63.5 ng/g weight (n = 51 and 13), respectively. The cumulative cancer risk among males was 10.4/100,000. The highest fraction of inorganic/total arsenic content in white rice ranged from 76.9 to 88.2 % and from 81.0 to 96.5 % in brown rice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…Exposure from rice has been assessed in a number of studies (U.S. Food and Drug Administration, 2016;Sand et al, 2015;Chen et al, 2016;Davis et al, 2017;Sun et al, 2012). These studies indicate that rice is the most common exposure source for food stuffs.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure from rice has been assessed in a number of studies (U.S. Food and Drug Administration, 2016;Sand et al, 2015;Chen et al, 2016;Davis et al, 2017;Sun et al, 2012). These studies indicate that rice is the most common exposure source for food stuffs.…”
Section: Introductionmentioning
confidence: 99%
“…With this scenario, either the overestimate or the lower estimate for the ADD of both genders is likely to happen. A study in Taiwan that focused on the iAs risk assessment from rice consumption showed that women were exposed to iAs with a lower ADD than men [50].…”
Section: Discussionmentioning
confidence: 99%
“…We further illustrate the usefulness of the TFR system in risk assessments of cadmium, a heavy metal that is harmful to the human body, in the rice in the composite food. Rice is one of the most popular food crops in Taiwan as well as in the Asia–Pacific region [6]. It may contain polluted substances accrued during the metabolic process if it is irrigated with polluted water and sediments.…”
Section: Introductionmentioning
confidence: 99%